PGC1α overexpression preserves muscle mass and function in cisplatin‐induced cachexia. Issue 5 (28th July 2022) - Huot, Joshua R.; Pin, Fabrizio; Chatterjee, Rohit; Bonetto, Andrea
Abstract: Background: Chemotherapy induces a cachectic‐like phenotype, accompanied by skeletal muscle wasting, weakness and mitochondrial dysfunction. Peroxisome proliferator‐activated receptor‐gamma coactivator‐1 alpha (PGC1α), a regulator of mitochondrial biogenesis, is often reduced in cachectic skeletal muscle. Overexpression of PGC1α has yielded mixed beneficial results in cancer cachexia, yet investigations using such approach in a chemotherapy setting are limited. Utilizing transgenic mice, we assessed whether overexpression of PGC1α could combat the skeletal muscle consequences of cisplatin. Methods: Young (2 month) and old (18 month) wild‐type (WT) and PGC1α transgenic male and female mice (Tg) were injected with cisplatin (C; 2.5 mg/kg) for 2 weeks, while control animals received saline ( n  = 5–9/group). Animals were assessed for muscle mass and force, motor unit connectivity, and expression of mitochondrial proteins. Results: Young WT + C mice displayed reduced gastrocnemius mass (male: −16%, P  < 0.0001; female: −11%, P  < 0.001), muscle force (−6%, P  < 0.05, both sexes), and motor unit number estimation (MUNE; male: −53%, P  < 0.01; female: −51%, P  < 0.01). Old WT + C male and female mice exhibited gastrocnemius wasting (male: −22%, P  < 0.05; female: −27%, P  < 0.05), muscle weakness (male: −20%, P  < 0.0001; female: −17%, P  < 0.01), and loss of MUNE (male: −82%, P  < 0.01; female: −62%, P  < 0.05), suggesting exacerbated cachexia compared with younger animals. Overexpression of PGC1α had mild protective effects on muscle mass in young Tg + C male only (gastrocnemius: +10%, P  < 0.05); however, force and MUNE were unchanged in both young Tg + C male and female, suggesting preservation of neuromuscular function. In older male, protective effects associated with PGC1α overexpression were heighted with Tg + C demonstrating preserved muscle mass (gastrocnemius: +34%, P  < 0.001), muscle force (+13%, P  < 0.01), and MUNE (+3‐fold, P  < 0.05). Similarly, old female Tg + C did not exhibit muscle wasting or reductions in MUNE, and had preserved muscle force (+11%, P  < 0.05) compared with female WT + C. Follow‐up molecular analysis demonstrated that aged WT animals were more susceptible to cisplatin‐induced loss of mitochondrial proteins, including PGC1α, OPA1, cytochrome‐C, and Cox IV. Conclusions: In our study, the negative effects of cisplatin were heighted in aged animals, whereas overexpression of PGC1α was sufficient to combat the neuromuscular dysfunction caused by cisplatin, especially in older animals. Hence, our observations indicate that aged animals may be more susceptible to develop chemotherapy side toxicities and that mitochondria‐targeted strategies may serve as a tool to prevent chemotherapy‐induced muscle wasting and weakness.